PENGARUH COVID-19 TERHADAP KINERJA UMKM DIMODERASI INOVASI PADA UMKM DI BANDAR LAMPUNG - Listyaningsih, Erna; Sariningsih, Eka; Alansori, Apip (Jurnal Ilmiah Akuntansi Rahmaniyah, 2023)
The purpose of this study was to examine the effect of COVID-19 on MSME performance moderated by innovation. This study used the research subjects of banana chip SMEs in the Bandar Lampung banana chip center, which amounted to about 40 SMEs. Using an associative and quantitative approach, while the data was collected using a survey method, namely a questionnaire and analyzed using the Structural Equation Model (SEM) - Partial Least Square (PLS) method with Smart PLS. The results of this study found that there was a significant effect of the COVID-19 pandemic on the performance of MSMEs, but the existence of innovation did not strengthen the influence of the COVID-19 pandemic on the performance of MSMEs. This indicates that many factors affect the performance of SMEs. The increased performance of MSMEs will make a better contribution to the progress of MSMEs to be able to survive in any conditions.